FRI0109 Short-term monitoring of sonographic changes induced by a corticosteroid injection in metacarpophalangeal joint of rheumatoid arthritis patients: a pilot study. (15th June 2017) - Carlo, M Di; Roia, D; Matteo, A Di; Salaffi, F; Filippucci, E; Grassi, W
Abstract : Background: Intra-articular corticosteroid injection is a well-established procedure in the daily practice since many decades [1]. High-resolution ultrasound (US), considered as in vivo microscopy, has the potential to help to understand how drugs develop their anti-inflammatory properties inside the articular space [2]. Objectives: To provide a very tight sonographic monitoring of the changes in a single metacarpophalangeal (MCP) joint in rheumatoid arthritis (RA) patients after the administration of intra-articular corticosteroid. Methods: In this study we consecutively enrolled RA patients with active disease (Composite Disease Activity Index - CDAI >10), at least one tender and swollen MCP joint, and without contraindication to intra-articular corticosteroid injection (e.g. poor controlled diabetes). After the clinical evaluation that established the most clinically involved MCP joint to inject, patients underwent an US examination of the joint by an experienced sonographer. Synovitis was scored in grey scale (GS) in terms of joint space enlargement (measured at the level where the distance between the bone diaphysis and the joint capsule was greater), and power Doppler (PD) signal (scored by a semiquantitative method: 0 = no intra-articular flow, 1 = single vessel signal, 2 = confluent vessels, and 3 = vessel signal in more than 50% of the intra-articular area). After the baseline US assessment (T0), the MCP joints were injected with 20 mg triamcinolone acetonide under sonographic guidance. Sonographic follow-up was performed in five timepoints: two hours (T1) after the injection, four hours (T2), eight hours (T3), 24 hours (T4), and 48 hours after the injection (T5). Results: Fifteen patients (13 women), with a mean age of 62.5 years, completed the follow-up. The mean CDAI was 28.9, anti-citrullinated protein antibodies were present in 9 patients. At T5, in all the patients was detectable a global reduction of joint space enlargement, of intra-articular PD signal, and of the numerical rating scale (NRS) of pain at the joint injected (Table). However, in majority of the patients (n: 13), the joint space enlargement showed an increase in the T1 and T2 US examinations, and in four patients PD signal, compared to T0, increased within the eight hours after the injection. No major adverse events were registered. Conclusions: A single intra-articular corticosteroid injection, performed under US guidance, is a very fast treatment to reduce synovitis of the injected joint. In the hours next to the injection is common to reveal a rise of joint space enlargement together with that of PD signal score. References: Courtney P, Doherty M. Joint aspiration and injection and synovial fluid analysis. Best Pract Res Clin Rheumatol 2013;27:137–69. Filippucci E, Iagnocco A, Salaffi F, et al. Power Doppler sonography monitoring of synovial perfusion at the wrist joints in patients with rheumatoid arthritis starting adalimumab treatment. Ann Rheum Dis 2006; 65:1433–7. Disclosure of Interest: None declared